TINJAUAN PERLINDUNGAN HUKUM TERHADAP KONSUMEN ROKOK TANPA LABEL PERINGATAN KESEHATAN BERUPA GAMBAR BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (ANALISIS PUTUSAN NOMOR 410/PID.SUS/2020/PN BTM) - Angela Devina; Vera W. S. Soemarwi (Jurnal Hukum Adigama, 2021)
Cigarettes are currently not only known in the form of bars but also in the form of electric cigarettes or what is often also called vapor. In Indonesia, cigarettes are no longer foreign objects to be consumed but have become a habit of people to consume cigarettes. The government has tried to make various efforts to make people aware of how dangerous it is to consume cigarettes namely, the issuance of Government Regulation no. 109 of 2012 concerning the Safeguarding of Materials Containing Addictive Substances in the Form of Tobacco Products for Health, a Decree of the Head of the Food and Drug Monitoring Agency of the Republic of Indonesia (BPOM RI) is stipulated on the Procedure for Supervision of Circulating Cigarette Products and Advertising. Regarding health warnings in the form of pictures and writings that have one meaning that is printed together with the product packaging, it is very clear that it is te obligation of business actors as stated in Article 14 of Government Regulation no. 109 of 2012 and also regulated in Article 4 of Law Number 8 of 1999 concerning Consumer Protection and Article 7 of Law Number 8 of 1999 concerning Consumer Protection (hereinafter referred to as UUPK).